Evaluating Factors Influencing the Urban Waste Production Using Vikor Model and Fuzzy Analytical Hierarchy Analysis (Case Study: Gilan Province) - Camelia Alavi (Journal of Global Pharma Technology, 2018)
Solid wastes are inseparable part of human life, and production of these wastes in different quantities and qualities is one of the greatest environmental problems of current age. Different factors influence production of urban wastes, which identifying these factors and determining the importance of them make it possible to take necessary steps in this regard. Economic, social, and weather factors in each region can have a direct impact on waste production. Gilan province is one of the northern provinces of Iran. In light of its geographical and climatic conditions, it hosts great number of travelers every year, resulting in increased production of wastes in this province. On the other hand, the specific situation and conditions of this province, because of its proximity to Caspian Sea and high possibility of its contamination, developing an appropriate plan for waste management seems to be an essential. Thus, different factors influencing the production of urban waste in Gilan province were identified using previous studies and experiences of experts in this area, and they were weighted using fuzzy hierarchy analysis method. Finally, VIKOR model that is a multi-criterion decision model was used to prioritize them. Accordingly, information related to family income, GDP, population, family size, temperature, and wastes produced in Gilan province was collected, and the correlation coefficient of each of these factors with wastes produced in Gilan province was obtained. Findings revealed direct impact of family income, population, temperature, increasing daytime, and marginalization on waste production in Gilan province, while the social class and media education in Gilan province had a reverse impact on waste production. After prioritizing the methods, findings revealed that the first method, namely, recycling and compost, and the third method, namely, appropriate landfilling are the most suitable methods for this region, considering its geographical situation.Keywords: Effective factors, Urban wastes, Fuzzy Analytical Hierarchy Model, Fuzzy VIKOR method.